2014
DOI: 10.4236/fns.2014.56061
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Oxidant Status of Male Adults with and without Prostate Cancer in Ibadan, Nigeria

Abstract: Background: Recent studies show increasing prostate cancer incidence in Nigeria. Significant correlations identified between diet and prostate cancer occurrence, indicate that low antioxidant status could contribute to the aetiology of prostate cancer. Methods: This cross-sectional study determined selected antioxidants (lycopene, beta-carotene and retinol) status of 10 (Experimental group) and 17 (Control) male adults with and without PC, recruited from the Urological Section of the Surgical Out-patients' Dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(19 reference statements)
1
0
0
Order By: Relevance
“…In 2009, Oluyemi et al, [32] reported a similar finding with individual antioxidants such as superoxide dismutase, catalase and vitamin E which was also supported by the observations made by Sosanya et al, (2014) [33]. Meanwhile, from an earlier study we suggested that the reason for which there was no significant difference in the level of total antioxidant status was probably because subjects took enough antioxidants that protected them from oxidative stress as at the period of study [34].…”
Section: Discussionsupporting
confidence: 71%
“…In 2009, Oluyemi et al, [32] reported a similar finding with individual antioxidants such as superoxide dismutase, catalase and vitamin E which was also supported by the observations made by Sosanya et al, (2014) [33]. Meanwhile, from an earlier study we suggested that the reason for which there was no significant difference in the level of total antioxidant status was probably because subjects took enough antioxidants that protected them from oxidative stress as at the period of study [34].…”
Section: Discussionsupporting
confidence: 71%